Policy implications of public assets management for forest and wildlife conservation in Tanzania - Sobayi, Wenceslaus Mselya (2019)
This research aims at studying policy implications of public assets management for forest and wildlife conservation in Tanzania. The study has been conducted in Tanzania and the main subject areas of examination include: Tanzania foreign policy and how it affects donors’ financial and technical support in forest and wildlife management; the cooperation that exists between bureaucrats and other actors in designing and implementing policies; research studies and their contribution to the effectiveness of policy provisions; Government decentralisation policy and how it affects operational efficiency in managing forest and wildlife resources; and lastly, involvement of local communities in forest and wildlife management and its influence on their livelihood outcomes.